An Economic Model of Trade Credit - Schwartz, Robert A. (Journal of Financial and Quantitative Analysis, 1974)
In considering trade credit, we need to ask three questions:1. Why do nonfinancial firms commonly participate in the process of financial intermediation by extending credit to their customers?2. What explains differences in credit periods between firms and industries as well as over time for specific firms and industries?3. How do changing monetary conditions affect the credit that firms extend to their customers?To answer these questions, we first identify two reasons for credit sales: the first we might call a financing motive, and the second a transactions motive. The transactions motive can readily be understood—it costs something to match the time pattern of payment for goods with the time pattern of receipt of goods. Buyers benefit if bills are allowed to accumulate for periodic payment. Furthermore, trade credit gives buyers time to plan for the payment of unexpected purchases, enables them to forecast future cash outlays with greater certainty, and simplifies their cash management. To the extent that buyers benefit, sellers have an opportunity to sell credit. It is likely that, to a large extent, the aggregate stock of trade credit is explained by the transactions motive.